DNA vaccination against bcr-abl-positive cells in mice - Lucansky, Vincent; Sobotkova, Eva; Tachezy, Ruth; Duskova, Martina; Vonka, Vladimir (International journal of oncology, 2009)
A series of DNA vaccines based on the bcr-abl fusion gene were developed and tested in mice. Two mouse (BALB/c) bcr-abl-transformed cell lines, B210 and 12B1, which both expressed p210bcr-abl and were oncogenic for syngeneic animals but differed in some other respects, were used as a model system. In the first series of experiments, plasmids carrying either the complete bcr-abl fusion gene or a fragment thereof coding for a 25-amino acid-long junction zone (bcr-abl25aa) linked with genes coding for a variety of immunostimulatory factors were used as the DNA vaccines. A plasmid carrying the complete bcr-abl gene was capable of inducing protection against challenge with either B210 or 12B1 cells. However, the DNA vaccines based on the gene fragment coding for p25aabcr-abl did not induce significant protection. To localize the immunizing epitopes on the p210bcr-abl protein, the whole fusion gene was split into nine overlapping fragments and these, individually or in various combinations, were used for immunization. Although none of the vaccines based on any single fragment provided potent protection, some combinations of these fragment-based vaccines were capable of eliciting protection comparable to that seen after immunization with the whole-gene vaccine. Surprisingly, a mixture of six fragment-vaccines was more immunogenic than the complete set of fragment DNA vaccines. To analyze this phenomenon, the three fragments missing from the hexavaccine were either individually or in various combinations mixed with the hexavaccine. The results obtained suggested that the product of the fragment coding for 197 amino acids forming the N-terminal of the BCR protein was involved in the decreased immunogenicity. However, further experiments are needed to clarify the point. Additional experiments revealed that all the important epitopes were located in the ABL portion of the p210bcr-abl protein. The livers, spleens and bone marrows of the successfully immunized animals were tested for the presence of bcr-abl-positive cells by RT-PCR. The results were negative, this suggesting that these animals were free of any residual disease.
Keywords: Animals; HL-60 buňky; DNA vakcíny; transfekce; bcr-abl fúzní proteiny; časové faktory; Cancer Vaccines; Time Factors; Transfection; lidé; chronická myeloidní leukemie; Mice; Vaccines, DNA; HL-60 Cells; Mice, Inbred BALB C; myši; imunizace; peptidové fragmenty; Immunization; protinádorové vakcíny; Peptide Fragments; myši inbrední BALB C; Epitope Mapping; zvířata; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; mapování epitopu; Humans